Genetic Variations in the Human Angiotensin-ConvertingEnzyme 2 and Susceptibility to Coronavirus Disease-19 - Taravat Talebi; Tannaz Masoumi; Katayoun Heshmatzad; Mahshid Hesami; Majid Maleki; Samira Kalayinia (Genetics Research)
Background. Health and economies are both affected by the coronavirus disease-19 (COVID-19) global pandemic. Angiotensin-converting enzyme 2 (ACE2) is a polymorphic enzyme that is a part of the renin-angiotensin system, and it plays a crucial role in viral entry. Previous investigations and studies revealed that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and ACE2 have a considerable association. Recently, ACE2 variants have been described in human populations in association with cardiovascular and pulmonary conditions. In this study, genetic susceptibility to COVID-19 in different populations was investigated. Methods and Results. We evaluated the identified variants based on the predictive performance of 5 deleteriousness-scoring methods and the 2015 American College of Medical Genetics and Genomics (ACMG) guidelines. The results indicated 299 variants within the ACE2 gene. The variants were analyzed by different in-silico analysis tools to assess their functional effects. Ultimately, 5 more deleterious variants were found in the ACE2 gene. Conclusions. Collecting more information about the variations in binding affinity between SARS-CoV-2 and host-cell receptors due to ACE2 variants leads to progress in treatment strategies for COVID-19. The evidence accumulated in this study showed that ACE2 variants in different populations may be associated with the genetic susceptibility, symptoms, and outcome of SARS-CoV-2 infection.